A migração de venezuelanos para o Brasil: representações sociais e imaginários (socio)discursivos em narrativas de vida e textos jornalísticos - Maíra Ferreira Sant'Ana (2022)
The numbers of displacement in the world are the largest ever recorded in contemporary times. In 2019, 79.5 million people were forced to leave their homes due to persecution, conflict, violence, or human rights violations. In this scenario, the growth of migration flows of the population of Venezuela is notorious, characterizing, according to the UN Refugee Agency (2020), the largest exodus in the recent history of Latin America and one of the largest displacement crises in the world. In 2018, in Brazil, Venezuelans represented 77% of the refugee requests made. Given these data, we sought, in a first moment, to analyze life narratives of Venezuelan migrants internalized to Belo Horizonte-MG, which were collected through semi-structured interviews, in order to give the word to these subjects that, as a rule, are reduced to numbers and percentages and/or are “told” by others (politicians, journalists, experts etc.). Considering that this theme, besides being of the utmost relevance from the human and social point of view, is a phenomenon that frequently gains the focus of the media, we sought, in a second moment, to analyze the social representations and the sociodiscursive imaginaries that circulate in news that deal with the migration of Venezuelans to Brazil in two newspapers that we considered more representative for this research: Folha de Boa Vista, since it is through the state of Roraima that Venezuelans generally enter the country, and O Tempo, published in Belo Horizonte-MG, since Venezuelans, at the time the interviews were conducted, lived in the capital of Minas Gerais. Our goal, in this case, was to compare the representations and imaginaries that we apprehended in the reports of the Venezuelans interviewed with those manifested in the selected newspapers, in search of similarities and differences. For the corpus analysis (life narratives and news), we used some planes of the global semantics of D. Maingueneau (2008). The results obtained show that the approach of the newspaper O Tempo, regarding the representations under analysis, is closer to how the Venezuelan migrants represent themselves than the approach of the newspaper from Roraima, especially because the newspaper from Minas Gerais chooses to focus on the migrant subjects from the issues they experience in their migratory process, and not the problems (social, economic, etc.) that they represent to the host society, as Folha de Boa Vista does.